An Organization Development Intervention to Enhance the Learning Organization A Case Study of Student Affairs, Assumption University of Thailand - Kaipunlert, Tana (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
Higher education is evolving rapidly in today’s environment of global connectivity, technological advances and student diversity. The education industry must respond to these changes in order to remain viable. As a key division in the university, Student Affairs plays a vital role in helping universities respond to changes by ensuring that students’ needs are addressed effectively. To accomplish this, Student Affairs must continuously be able to improve by becoming skilled at creating, acquiring and transferring knowledge, in short, it must become a learning organization. The purpose of this study is to enhance the Student Affairs Division of Assumption University to become a learning organization by using organizational development methods including diagnostic procedures, organizational interventions and training programs. Qualitative and quantitative methods were utilized for this study. Data was collected through interviews and questionnaires. Pre-ODI analysis revealed that members of Student Affairs, although cognizant of the importance of some aspects of the learning organization, were not consistent in their behavior and actions. OD interventions were employed to increase both knowledge and behavior in regards to learning organization culture. They included team building, coaching, Appreciative Inquiry and SOAR workshops. Post-ODI analysis of the experimental and control groups using a paired samples t-test, supported by a calculation of Cohen’s effect size, revealed a significant difference in the total gain scores for Pre-ODI and Post-ODI results. The interventions were found to have an effective result in enhancing the learning organization culture in the Student Affairs Division of Assumption University.